High Expression of Antiviral and Vitamin D Pathway Genes Are a Natural Characteristic of a Small Cohort of HIV-1-Exposed Seronegative Individuals - Aguilar-Jimenez, Wbeimar; Saulle, Irma; Trabattoni, Daria; Vichi, Francesca; Lo Caputo, Sergio; Mazzotta, Francesco; Rugeles, Maria T.; Clerici, Mario; Biasin, Mara (Frontiers in Immunology, 2017)
Natural resistance to HIV-1 infection is influenced by genetics, viral-exposure and endogenous immunomodulators such as vitamin D (VitD), being a multifactorial phenomenon that characterizes HIV-1-exposed but seronegative individuals (HESNs). We compared mRNA expression of 10 antivirals, 5 immunoregulators, and 3 VitD pathway genes by qRT-PCR in cells of a small cohort of 11 HESNs, 16 healthy-controls (HCs) and 11 seropositives (SPs) at baseline, in response to calcidiol (VitD precursor) and/or aldithriol-2-(AT2)-inactivated HIV-1. In addition, the expression of TIM-3 on T and NK cells of 6 HCs after calcidiol and calcitriol (active VitD) treatments was evaluated by flow cytometry. Calcidiol increased the mRNA expression of HAVCR2 (TIM-3; Th1-cells inhibitor) in HCs and HESNs. AT2-HIV-1 increased the mRNA expression of the activating VitD enzyme CYP27B1, of the endogenous antiviral proteins MX2, TRIM22, APOBEC3G, and of immunoregulators ERAP2 and HAVCR2, but reduced the mRNA expression of VitD receptor (VDR) and antiviral peptides PI3 and CAMP in all groups. Remarkably, higher mRNA levels of VDR, CYP27B1, PI3, CAMP, SLPI, and of ERAP2 were found in HESNs compared to HCs either at baseline or after stimuli. Furthermore, calcitriol increase the percentage of CD4+ T cells expressing TIM-3 protein compared to EtOH controls. These results suggest that high mRNA expression of antiviral and VitD pathway genes could be genetically determined in HESNs more than viral-induced at least in PBMCs. Moreover, the virus could potentiate bio-activation and use of VitD, maintaining the homeostasis of the immune system. Interestingly, VitD induced TIM-3 on T cells, a T cell inhibitory and anti-HIV-1 molecule, requiring further studies to analyze the functional outcomes during HIV-1 infection.